A proposed vision of the role of the Educational Supervisor specialized in the development of education teachers Sports in Mosul during the Koruna pandemic from their point of view - م.د. ذاكر محفوظ حامد الدليمي أ.د رياض احمد اسماعيل الاشريفي (physical education and sport sciences college for women/ Baghdad University, 2021)
The research aims to: - 1- Identify the level of the proposed role that the superintendent can play in the educational competence towards the development of secondary school sports education teachers in Mosul during the Corona pandemic from their point of view. 2- Develop a proposed concept of the role of the supervisor of educational competence in the development of sports education teachers during the Corona pandemic. The descriptive method was used in the scanning method and included the study sample. (87) A teacher of sports education for boys' secondary schools in Mosul, and to obtain data, a questionnaire form was designed for the proposed role of the supervisor of educational competence towards the development of sports education teachers during the Corona pandemic in three dimensions: (Cognitive development, management development, technological development) and applied after scientific conditions of sincerity and persistence, data have been dealt with statistically through the computational medium, standard deviation, percentage, simple Pearson correlation, Spearman-Brown equation, Getman equation and alpha-Cronbach coefficient                                                                                      : The researchers concluded that 1- The professional educational supervisor may offer his/her tasks at a positive level in the development of sports education teachers in Mosul during the Corona pandemic from their point of view in accordance with the dimensions of cognitive, administrative and technological development 2- The proposed concept of the role of an educational specialist (sports education) in the development of sports education teachers during the Corona pandemic has been developed in accordance with the dimensions of cognitive, administrative and technological development. The researchers recommended some of these recommendations   : 1- The need for the supervisor of educational competence to develop sports education teachers in the light of a supervisory role commensurate with the health situation resulting from the Corona pandemic, including the dimensions of cognitive, administrative and technological development..  2- The possibility for the Supervisor of Educational Competence (Sports Education) to apply the proposed concept reached in this study of the supervisory role it can play in the development of sports education teachers during the Corona pandemic.